2018
DOI: 10.1620/tjem.246.121
|View full text |Cite
|
Sign up to set email alerts
|

Infant Suffocation Incidents Related to Co-Sleeping or Breastfeeding in the Side-Lying Position in Japan

Abstract: Co-sleeping and breastfeeding in the side-lying position have recently been pointed out as risk factors for suffocation in sleeping infants; however, there is no actual report on an "incident." "Incident" is defined as a tense or sobering experience without a consequential fatal suffocation accident. It is important to understand infant suffocation incidents to prevent accidents during co-sleeping and breastfeeding in the side-lying position. We investigated factors and frequency of infant suffocation incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…In our study, we found that the incidence of accidental suffocation and strangulation in bed was higher in winter, which is similar to American and Japanese reports [ 21 , 37 ] We also found that 93.8% of cases reportedly experienced accidental suffocation and strangulation while the infants were cosleeping with their parents, which was similar to findings reported from previous surveys [ 38 ]. However, the extent of cosleeping in China is 57.8% [ 39 ], which is much higher than that in developed countries: 20–30% of mothers in the UK [ 40 ], 13.5–40% in the US [ 41 ], and 8.8–19% in New Zealand [ 9 ]. Takatsu et al estimated that the mortality associated with infants who were cosleeping was 10.2 times higher than that of those who were not cosleeping [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the incidence of accidental suffocation and strangulation in bed was higher in winter, which is similar to American and Japanese reports [ 21 , 37 ] We also found that 93.8% of cases reportedly experienced accidental suffocation and strangulation while the infants were cosleeping with their parents, which was similar to findings reported from previous surveys [ 38 ]. However, the extent of cosleeping in China is 57.8% [ 39 ], which is much higher than that in developed countries: 20–30% of mothers in the UK [ 40 ], 13.5–40% in the US [ 41 ], and 8.8–19% in New Zealand [ 9 ]. Takatsu et al estimated that the mortality associated with infants who were cosleeping was 10.2 times higher than that of those who were not cosleeping [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is now time to admit that some cases of accidental suffocation have been labelled as SIDS. 14 If we are to prevent deaths due to infants being overlaid and suffocated, we must explore the infants' sleeping environments, through clinical and mandatory death scene investigations, with the help of forensic pathologists. Countries where this is mandatory have shown that the incidence of SIDS has declined and accidental suffocation has increased, due to more information about the circumstances surrounding the death.…”
Section: Discussionmentioning
confidence: 99%
“…Such co-sleeping is a common style of sleep. Tokutake et al [17] reported that 84% of mothers practice co-sleeping, of whom half also practice breastfeeding. The father was found to be the first responder in up to 20% of cases, and in most of these cases the father also co-slept and discovered the infant death upon awakening.…”
Section: Plos Onementioning
confidence: 99%
“…However, 40% of infants were found in the prone position, of which frequency was higher than that reported in an earlier study. [17] Li et al [31] reported that 60% of SIDS infants were found in the prone position in the United States. It is possible that turning over by infants during sleep is a causal factor.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation